Dysregulation of Blood-Brain Barrier and Exacerbated Inflammatory Response in Cx47-Deficient Mice after Induction of EAE - Stavropoulos, Filippos (Pharmaceuticals (Basel), 2021)
Induction of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), in connexin 32 (Cx32) or Cx47 knockout (KO) mice with deficiency in oligodendrocyte gap junctions (GJs) results in a more severe disease course. In particular, Cx47 KO EAE mice experience an earlier EAE onset and more pronounced disease severity, accompanied by dysregulated pro-inflammatory responses preceding the disease manifestations. In this study, analysis of relevant pro-inflammatory cytokines in wild type EAE, Cx32 KO EAE, and Cx47 KO EAE mice revealed altered expression of Vcam-1 preceding EAE [7 days post injection (dpi)], of Ccl2 at the onset of EAE (12 dpi), and of Gm-csf at the peak of EAE (24 dpi) in Cx47 KO EAE mice. Moreover, Cx47 KO EAE mice exhibited more severe blood-spinal cord barrier (BSCB) disruption, enhanced astrogliosis with defects in tight junction formation at the glia limitans, and increased T-cell infiltration prior to disease onset. Thus, Cx47 deficiency appears to cause dysregulation of the inflammatory profile and BSCB integrity, promoting early astrocyte responses in Cx47 KO EAE mice that lead to a more severe EAE outcome. Further investigation into the role of oligodendrocytic Cx47 in EAE and multiple sclerosis pathology is warranted.